Al2O3 decorated with polyhedral silsesquioxane units: An unconventional filler system for upgrading thermal conductivity and mechanical properties of rubber composites. (3rd May 2023) - Mirizzi, Lorenzo; D'Arienzo, Massimiliano; Nisticò, Roberto; Fredi, Giulia; Diré, Sandra; Callone, Emanuela; Dorigato, Andrea; Giannini, Luca; Guerra, Silvia; Mostoni, Silvia; Di Credico, Barbara; Scotti, Roberto
Abstract: The present study reports on the development and exploitation of an original filler system, based on alumina nanoparticles (NPs) and polyhedral silsesquioxane (POSS) units, namely Al2 O3 @POSS, where the remarkable compatibilization and thermomechanical features imparted by the silsesquioxane cage units "makes an alliance" with the enhanced thermal conductivity of Al2 O3 NPs. The target is to supply rubber nanocomposites with improved heat transport and mechanical properties potentially applicable in tires formulation. The hybrid filler was prepared by a double-step approach consisting of a first silanization of Al2 O3 with a methacrylate silane and subsequent grafting of OctaMethacrylPOSS through a radical reaction mediated by dicumyl peroxide as radical initiator. The material was characterized in depth in terms of structure, surface, and morphology and then used for producing, by solvent-casting technique, polybutadiene composites. The idea is to supply and test a model alumina-rubber based system which allows to better unveil the role played by the silsesquioxane units, thanks to the absence of other components (i.e. rubber polymers, vulcanization curatives and filler) usually included in real rubber formulations for tires. The comprehensive thermomechanical and morphological characterization of the nanocomposites highlighted the key role played by POSS units decorating the alumina surface, which assure both the compatibility between filler and polymer host, and an homogeneous distribution and continuous networking of the alumina NPs. This positively influences not only the heat transport, providing thermal conductive pathways that raise the thermal diffusivity even at low filler loadings (+60–70% with respect to composite enclosing bare alumina at a concentration of 15–10 v/v %) but also the storage modulus, paving the way toward a potential exploitation of Al2 O3 @POSS hybrid filler in large-scale formulations of rubber composites, namely those employed for tires. Graphical abstract: Image 1